Selective Quantification of Organic and Inorganic Arsenic in Kelp Thalli and Kelp-Based Products - V. M. Shchukin; A. A. Erina; Yu. N. Shvetsova; E. S. Zhigilei; N. E. Kuz’mina (Регуляторные исследования и экспертиза лекарственных средств, 2023)
Kelp can accumulate large quantities of arsenic compounds even in the absence of considerable environmental pollution. A substantial difference in toxicity between organic and inorganic arsenic compounds makes the form of arsenic relevant for the risk assessment of consuming kelp thalli and kelp-based products.The aim of the study was to develop an analytical procedure for the selective quantification of organic and inorganic arsenic in kelp thalli by inductively coupled plasma mass spectrometry and solid-phase extraction without scheduled precursors.Materials and methods. The authors studied samples of Laminaria saccharina and Laminaria japonica, spiking mixtures of chemical compounds containing arsenic in different oxidation states, and bioactive dietary supplements based on kelp thalli. Solid-phase extraction was performed using Maxi-Clean SAX cartridges. The arsenic content was determined using an Agilent 7900 inductively coupled plasma mass spectrometer.Results. Microwave-assisted extraction with deionised water ensures 91% recovery of arsenic-containing compounds from kelp thalli, and the addition of hydrogen peroxide to the extractant provides complete extraction. Solid-phase extraction with an eluent based on 3% H2O2 can extract the organic fraction from a mixture of organic and inorganic arsenic compounds without washing the inorganic fraction off the cartridge.Conclusions. The authors offer an effective analytical procedure for the selective quantification of organic and inorganic arsenic in kelp thalli and kelp-based products. This procedure allows for the isolation of arsenic-containing compounds from the organic matrix of kelp with 3% hydrogen peroxide. Solid-phase extraction with this extractant can effectively separate organic and inorganic fractions without prior neutralisation of the test solution.